Efficacy of electrical vestibular stimulation (VeNS) on adults with insomnia: A double-blind, randomized, sham-controlled trial - Teris Cheung; Joyce Yuen Ting Lam; Kwan Hin Fong; Calvin Pak-Wing Cheng; Yu-Tao Xiang; Tim Man Ho Li (Dialogues in Clinical Neuroscience, 2025)
Introduction Insomnia, a widespread sleep disorder, affects a significant portion of the global population. This study is the first in Asia to evaluate the efficacy of electrical vestibular stimulation (VeNS) as a treatment for insomnia in Hong Kong adults, addressing a gap in non-pharmacological interventions.Methods A double-blind, randomized, sham-controlled trial was conducted with 101 adults exhibiting insomnia symptoms. Participants were randomized into active VeNS or sham groups (1:1 ratio) and underwent twenty 30-minute VeNS sessions over four weeks. Psychological outcomes, including insomnia severity, sleep quality, and quality of life were assessed at baseline (T1), post-intervention (T2). Follow-up assessments were conducted at one- (T3) and three-month (T4) to evaluate the sustainability of VeNS effects.Results Of 83 participants (40 VeNS and 43 sham-VeNS), the VeNS group showed significant reductions in insomnia severity at T2 (p = 0.03, d = -0.47) and T4 (p = 0.02, d = -0.32), alongside improved quality of life (i.e., role-physical) at T2.Conclusion VeNS is a novel, non-invasive and safe neuromodulation device that may serve as an adjunct treatment for primary insomnia. The present findings provide a foundation for future multisite comparison studies to further evaluate VeNS efficacy.Trial registration ClinicalTrials.gov Identifier: NCT04452981